Mencegah Bahaya Seks Bebas Pada Remaja di SMAN 6 Kota Bengkulu - Andri Kusuma Wijaya; Susilawati; M. Bagus Andrianto; Fatsiwi Nunik Andari (JURNAL PENGABDIAN KESEHATAN, 2023)
Free sex is sexual relations carried out by men and women without any marriage ties. Free sex behavior is currently a problem experienced by Indonesian teenagers. Today's youth are easily influenced by calls from the opposite sex to commit sexual deviance driven by mutual love for one another. Teenagers never think that they will lose what they will receive if they have sex outside of marriage. A recent survey conducted by the Indonesian Child Protection Commission (KPAI) showed that 32% of adolescents aged 14 to 18 in Jakarta, Surabaya and Bandung had had sex. as many as 21.2% of young women in Indonesia have had an abortion. Islam has regulated the relationship between men and women. Islam prohibits a child from being introduced to his identity as a man or a woman, the boundaries of genitalia and manners as well as basic social norms so that they can form a believer and pious person. Apart from being a form of education, this is a form of prevention against crimes and sexual deviations.